Expert secrets : the underground playbook for creating a mass movement of people who will pay for your advice - Brunson, Russell (Russell C.) (Tantor Media, Inc., 2018)
Your message has the ability to change someone's life. The impact that the right message can have on someone at the right time in their life is immeasurable. It could help to save marriages, repair families, change someone's health, grow a company, or more...But only if you know how to get it into the hands of the people whose lives you have been called to change. Expert Secrets will put your message into the hands of people who need it.